Comparative Assessment of Various Concentration and Exposure Time of Sodium Dodecyl Sulfate as Decellularization Agents for Small-Vessels Vascular Tissue Engineering - Sembiring, Yan Efrata; Ledyastatin, Rafaela Andira; Nurrahmah, Atiya; Sulistyaningsih, Ni Kadek; Sinatra, Jeconia Agrippina Ruth; Puruhito, Ito; Suroto, Heri (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Finding the optimum vascular grafts (VG) to replace damaged blood arteries in cardiac surgery is still a work in progress. To be employed, a tissue-engineered VG (TEVG) must have the appropriate biological and mechanical qualities. Decellularized arteries may be a better TEVG than synthetic grafts because of their natural three-dimensional architecture. AIM: The goal of this study was to compare different concentrations and times of sodium dodecyl sulfate (SDS) to decellularize tissue to find the best decellularized VG. METHODS: In all decellularized scaffolds, which are 1% SDS-2 weeks group, hematoxylin and eosin and Masson’s trichrome staining exhibited looser collagen networks and fewer nuclei. RESULTS: The orientation of collagen fibers was identical to native vascular scaffolds. Collagen I deposition was seen in the immunohistochemistry assay. A tensile strength test revealed that the decellularized scaffold (0.5% SDS for 4 weeks and 0.5% SDS for 2 weeks) had exceeded the native arteries’ maximal strength. In comparison to 1% SDS in 4 weeks treated groups, scanning electron microscopy following decellularization revealed no endothelial cells on the inner side of 1% SDS in 2 weeks group with minimum extracellular matrix damage. The endothelial cells remained marginally visible on the inner side of all 0.5% SDS treated groups. The 3-(4,5-dimethylthiazol-2yl)2,5-diphenyltetrazolium bromide test was used to determine the cytotoxicity of the decellularized scaffolds. CONCLUSION: This study reveals that exposing a bovine mesenteric artery to 1% SDS for 2 weeks is an excellent procedure for extracting the most acellular VG, potentially serving as a biological scaffold for TEVGs.